A Ride in the Park: Remembering West Glacier and the Graham-Paige - Reilly, Marili Green; United States. Department of Transportation. Federal Highway Administration. Office of Federal Lands Highway
In 2008, the Federal Lands Highway Program celebrates its 25th Anniversary. Looking back at the past quarter century – and more – a number of retirees have shared their stories about life in the Vancouver office and in the field.